Peran keterlibatan orang tua terhadap kesiapan sekolah pada anak prasekolah - Thifal Hanifah (Fakultas Psikologi, 2019)
Preschool children will pass transitions period from Kindergarten into elementary school which has new requirements. Transition period can work efficiently if children have had the preparation of “ready for school”. The factors which influence the school readiness is the involvement of parents. Parental involvement is needed because it will create continuity between children's education at home and at school. This research aimed to determine the effect of parental involvement on school readiness in preschool children. This research method used quantitative methods with a sampling technique of random sampling. The subjects of the research were parents who had preschool children of 100 respondents. The instrument used the PIQ and SRQ (Indonesian standard). Data analysis used simple linear regression test. The results showed F value = 33.211, p < 0.01 that there was positive effect on parents’ involvement toward significant school readiness with home-based involvement having strong relations from other dimensional.